Dimensional precision and surface roughness on turning tubes in fibre reinforced plastics based on the design experiments. (12th May 2004) - Davim, J. Paulo; Reis, Pedro
This paper presents a study of the cutting parameters (cutting velocity and feed) on dimensional precision and surface roughness in turning tubes of fibre reinforced plastics (FRP). A plan of experiments, based on the techniques of Taguchi, was performed machining with cutting parameters prefixed in composite workpiece. An orthogonal array and the analysis of variance (ANOVA) are employed to investigate the cutting characteristics of FRP (glass fibre-reinforced filament-wound tubes) using cemented carbide (K15) cutting tools. The objective was to establish a correlation between cutting velocity and feed with the surface roughness and the international dimensional precision (IT) in composite workpiece. The correlation was obtained by multiple linear regression. Finally, confirmation tests were performed to make a comparison between the experimental results foreseen from the mentioned correlation.